Equal split in the informal market for group train travel - Israel Waichman; Artem Korzhenevych; Till Requate (Kiel Institute for the World Economy (IfW), 2010)
In this paper we make use of a unique dataset collected in the central train station of Kiel, Germany. A group ticket is used by individual proposers who search for co-travelers to share the ride with shortly before the train departure. The bargaining behavior resembles the Ultimatum game to the extent that proposers request a fixed price for a shared ride and potential co-travelers usually accept or reject the deal. We observe that the prevailing price corresponds to the equal split of the ticket cost between the maximum possible number of co-travelers. This result is remarkable because the positions of the bargaining parties are hardly symmetric and the formation of the full group is not guaranteed. Using a simple agent-based model we are able to identify some sufficient conditions leading to the observed distribution of prices. Finally, we observed that the probability to accept an unusually high offer is decreasing with the price and increasing when the offer is made right before the train departure.
Keywords: C78; C93; D74; D83; 330; Natural field experiment; bargaining; focal point; equal split; agent-based model; Eisenbahntarif; Soziale Gruppe; Eisenbahnpersonenverkehr; Verhandlungstheorie; Ultimatumspiel; Feldforschung; Agent-based Model; Theorie; Deutschland